2018
DOI: 10.1016/j.est.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study of the thermocline filler concept based on exergy

Abstract: In this work, an extensive parametric study of the molten salt thermocline storage concept with filler is presented. The parametric study is coupled with an optimization routine, allowing a better comparison, since it finds only those storage configurations, which can directly substitute the two-tank system in a given power plant. Results show that, compared to the two-tank molten salt system, the thermocline technology achieves high exergetic efficiency at only slightly increased storage volume size and a hug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The thermocline region, where the temperature drop is located, causes exergy losses due to the contact of two fluids at different temperatures. Narrower thermocline regions produce lower exergy losses, as was reported by [10,59,60]. Nonetheless, despite the energy stored, those exergy losses cause the thermocline tanks to discharge lower energy compared to the two-tank technology, which does not present exergy losses because it has no temperature difference, and the efficiency is higher [9,11].…”
Section: Comparison Between Thermocline and The Two-tank Conceptmentioning
confidence: 78%
“…The thermocline region, where the temperature drop is located, causes exergy losses due to the contact of two fluids at different temperatures. Narrower thermocline regions produce lower exergy losses, as was reported by [10,59,60]. Nonetheless, despite the energy stored, those exergy losses cause the thermocline tanks to discharge lower energy compared to the two-tank technology, which does not present exergy losses because it has no temperature difference, and the efficiency is higher [9,11].…”
Section: Comparison Between Thermocline and The Two-tank Conceptmentioning
confidence: 78%
“…Xu et al analysed the exergetic efficiency in a cascaded system with three tanks containing different PCMs in series and deduced that the increase in HTF inlet temperature or the NTU of the HTF enhances the overall exergetic efficiency. Odenthal et al numerically investigated the molten salt thermocline storage systems with basalt rock as a filler material. The results showed that the thermocline storage has a superior exergetic efficiency compared to the separate two‐tank TES.…”
Section: Introductionmentioning
confidence: 99%